Increasing Procedure Text Reading Comprehension by using the Saintific Approach of Pictural Media for Students with Hearing Impairment - Renni Puji Hastuti; Muhari Muhari (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2017)
Reading skill have to be mastered by hearing impairment students, however, they face some difficulties in reading comprehension. This study was aimed at obtaining an overview of the learning process and finding the improvement skills of Procedure Text reading comprehension through the scientific approach of pictural media for hearing impairment students in the grade XI. The research design was a Classroom Action Research (CAR) with Kemmis & Mc Taggart spiral model. The implementation was done in two cycles. Planning in cycle I was done by creating a lesson plan reflecting the steps of observing, questioning, gathering information, associating, and communicating the picture as a medium. Repairing the 2nd cycle was by enlarging the media image with A2 paper size and giving scaffolding in the step of asking. The implementation was done according to the scientific approach steps: (1) observing: the students read and observe text & picture simultaneously, (2) asking: the students ask manythings that have not been understood yet, (3) gathering information: the students are active to find out, work together finding in the dictionary and experiencing hands-made sandwich (4) associating: the students associate all the information acquired and the previous experiences by making a text translation, (5) communicating: the students communicate the work in front of their friends . The successfull indicator achieved in cycle I was 25% of the students and in cycle II increased to 100%. It was concluded that the scientific approach of image media in learning for Procedure Text reading comprehension was succeeded in improving the students’ learning achievement of hearing impairment students of class XI in SLB N 2 Bantul.Keterampilan membaca harus dikuasai oleh siswa tuna rungu, walaupun mereka mengalami kesulitan dalam membaca pemahaman. Penelitian ini bertujuan untuk mendapatkan gambaran umum tentang proses pembelajaran dan menemukan keterampilan peningkatan pemahaman bacaan Procedure Text melalui pendekatan ilmiah media gambar untuk siswa tuna rungu di kelas XI. Desain penelitiannya adalah Penelitian Tindakan Kelas (SPG) dengan model spiral Kemmis & Mc Taggart. Implementasinya dilakukan dalam dua siklus. Perencanaan dalam siklus I dilakukan dengan membuat rencana pelajaran yang mencerminkan langkah-langkah mengamati, mempertanyakan, mengumpulkan informasi, bergaul, dan mengkomunikasikan gambar sebagai media. Pada perbaikan siklus ke-2 adalah dengan memperbesar produk dengan ukuran kertas A2 dan memberi scaffolding pada langkah bertanya. Implementasi dilakukan sesuai dengan langkah-langkah pendekatan ilmiah: (1) mengamati: siswa membaca dan mengamati teks & gambar secara bersamaan, (2) bertanya: siswa menanyakan banyak hal yang belum dipahami, (3) mengumpulkan informasi: siswa aktif untuk mencari tahu, bekerja sama menemukan di kamus dan pengalaman membuat sendiri sandwich, (4) bergaul: para siswa mengasosiasikan semua informasi yang diperoleh dan pengalaman sebelumnya dengan membuat terjemahan teks, (5) berkomunikasi: siswa mengkomunikasikan pekerjaan di depan teman mereka. Indikator keberhasilan yang dicapai pada siklus I adalah 25% siswa dan pada siklus II meningkat menjadi 100%. Disimpulkan bahwa pendekatan ilmiah produk gambar dalam pembelajaran untuk membaca teks bacaan Procedure Text berhasil meningkatkan prestasi belajar siswa tuna rungu kelas XI di SLB N 2 Bantul.